Identifizierung der Argumentationsindikatoren anhand der Regel der Gerechtigkeit und des Grundsatzes der Gegenseitigkeit - Buć, Bartosz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The authors of the pragma-dialectical theory of argumentation, van Eemeren and Grootendorst, distinguish between three argumentation schemes, i.e. symptomatic argumentation, causal argumentation and analogy argumentation. Moreover, they have created a catalogue of English words and phrases that are typical of the particular scheme and are called argumentative indicators. Their presence in a text can serve as an indication of the fact that an argument is being advanced. The present paper attempts to examine and list indicators of subtypes of the analogy argumentation in German.
Keywords: argumentative indicators; rule of justice; principle of reciprocity; analogy argumentation